Monitoring the effect of motivation on mastering knowledge and skills in distance learning systems - Miljković, Boža D.; Žižović, Mališa R.; Petojević, Aleksandar V. (Vojnotehnički glasnik / Military Technical Courier, 2016)
This paper describes how motivational processes affect students from the point of view of acquiring knowledge and skills, transfering them and using them in distance learning systems. Research in the social-cognitive framework illustrates the flexibility of the system and adequate adjustment of motivational patterns. A model of motivational processes, based on research, is presented as a function of learning objectives.The didactic-methodical approach to teaching was changed and adapted parallelly with monitoring the impact of the motivational factor on cognitive task performance and on students’ responses, i.e. with the motivational factor influence on the success or failure of the cognitive outcome and the learning process quality. This work investigated the influence of specific knowledge areas and the interests of students on understanding professional or scientific lectures. The implications in practice and interventions done through the design of software of distance learning systems were aimed at correcting the educational process.Two forms of prior knowledge (expert knowledge and general thematic knowledge) were checked at the start as entrance tests and a preparatory course. After problem solving, a feedback analysis was carried out to determine the effects of prior professional knowledge, general thematic knowledge and interests on understanding and solving problems. The  analysis of the results showed that for solving professional and technical tasks, prior knowledge of the domain, general thematic knowledge and interests were significant predictors of understanding and success.
Keywords: motivation; learning; cognitive functions; emotions; prior knowledge; distance learning; affectivity